Strategi Pembelajaran Kontekstual dalam Pengembangan Kompetensi Kebahasaan Siswa: Studi Kasus di MAN 2 Muaro Jambi - Silitonga, Delta OKtarin; Sophia Rahwamati (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
This study highlights the implementation of contextual learning strategies in Indonesian language instruction as an effort to develop students' language competence at MAN 2 Muaro Jambi. Using a descriptive qualitative approach, this research examines how teachers integrate real-life contexts into language learning, students’ responses to these methods, and the challenges encountered during the implementation process. The results show that contextual strategies not only enhance students’ language understanding and skills, but also motivate them to participate more actively in learning. However, obstacles such as differences in students’ language abilities and limited instructional time persist. This study recommends the need for sustained support for teachers in developing context-based language instruction.